Zapomniany młodopolski twórca wszechstronny - Strugińska, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article presents the profile of Zdzisław Dębicki, one of the less known Polish writers of Modernism and the early interwar period. The author outlines the state of research on the writer’s diverse literary output and, on the basis of few available sources, attempts to reconstruct Dębicki’s biography that is closely related to the contemporary history of his homeland. Summarizing and quoting the artist’s most important works, the author of this article characterizes the poet, diarist and literary critic as a representative of artistic circles of the late 19th-century Lviv and the early 20th-century Warsaw. The aim of this article is to introduce Dębicki’s writing as worth noticing and popularizing; writing that does not deserve its simplified reputation of being epigonic or worthless.